The safety of invasive prenatal diagnosis in women with HIV. (18th April 2012) - Nanda, S; Issa, R; Sankaran, S; Harding, K
Abstract : Introduction: Mother to child transmission (MTCT) of HIV is negligible (UK 0.1%) in women on highly active antiretroviral therapy (HAART). In those who are screen positive for trisomy 21, the issue is whether or not to proceed to invasive prenatal diagnosis (iPD). There are only 3 CVS and 5 cordocentesis in women on HAART reported in the world literature. The aim of our study is to highlight the need for HIV testing prior to iPD and to investigate the risk of MTCT in women on HAART having iPD. Methods: The notes of all women with HIV delivering at a single centre between January 2004 and October 2011 were reviewed; details of prenatal screening were extracted. Results: 326/530 (61%) women with HIV had screening for trisomy 21. Nine (2.7%) were screen positive (risk >1:250), two declined iPD. In two cases, HIV status was not known prior to the iPD. There were no cases of MTCT. Conclusion: CVS may be safe in women with HIV but further data is required. We recommend that data on iPD is routinely collected for the National Study of HIV in Pregnancy and Childhood database. Knowledge of the woman's HIV status will allow steps to be taken to rapidly reduce the viral load prior to iPD.